KEADILAN DALAM OPTIK HUKUM ALAM DAN POSITIVISME HUKUM - Achmad Soeharto (LPPM Universitas Pekalongan, 2022)
Natural law always measures and evaluates law in terms of justice, justice is an inseparable part of law, therefore the essence of law is justice. If the law is not fair, then according to natural law it is not law. Meanwhile, legal positivism measures and evaluates the law from the perspective of formal justice. The priority of justice as in natural law, is not a priority in legal positivism. For legal positivists, the most important thing is what the law is, not how the law should be. Even outside the law there is no law, the law must be in written form, to be able to provide legal certainty. With the different points of view of the two schools of law, until now there is no common ground between natural law and legal positivism in formulating justice. Each is adamant and differs in determining justice. Natural law is always ideal and places justice in the highest place. Justice is a priority that is non-negotiable and becomes the spirit of the law. Therefore the law must be fair and just is a constitutive element rather than the law. Meanwhile, justice in the perspective of legal positivism is limited to formal justice/procedural justice, or in other words, formalism justice that prioritizes form (written law)